2020
DOI: 10.21203/rs.3.rs-73069/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Sagittal Plane Inclination on Posterior Tibial Slope in Medial Open Wedge HTO – Experimental Study With a Square Column Model-

Abstract: Background: Medial open-wedge high tibial osteotomy (MOWHTO) is an effective and safe treatment method in medial osteoarthritis of knee. However, it may accompany unintended change of posterior tibial slope (PTS). Several factors are known to cause PTS change after MOWHTO. However, there is a lack of research on the sagittal plane osteotomy inclination (SPOI). The purpose of this study was to evaluate that SPOI affected the change in PTS. The hypothesis was that parallel SPOI causes no PTS change after MOWHTO.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Following the publication of the original article [ 1 ] the authors found that panels b and d in Fig. 3 have the same image.…”
mentioning
confidence: 98%
“…Following the publication of the original article [ 1 ] the authors found that panels b and d in Fig. 3 have the same image.…”
mentioning
confidence: 98%